Hubungan Antara Status Gizi dengan Kejadian Pneumonia pada Balita Di Wilayah Kerja Puskesmas Woha Tahun 2022 - Wahidah Wahidah (Barongko: Jurnal Ilmu Kesehatan, 2022)
Pneumonia is an acute infection of the lung tissue caused by bacteria, viruses, fungi, chemical exposure or physical damage to the lungs. The bacteria that commonly cause pneumonia are Streptococcus and Mycoplasma Pneumonia, while viruses that cause pneumonia are Adenoviruses, Rhinoviruses, Influenza Virus, Respiratory Syncytial Virus (RSV). This study aims to determine the relationship between nutritional status and the incidence of pneumonia in toddlers in the working area of the Woha Health Center. This type of research is an analytic observation research method with a cross sectional approach. This research was conducted in several working areas of the Woha Health Center. The research was conducted in January 2022. The population in this study were all toddlers who visited the Woha Health Center. The sampling technique uses simple random sampling of 50 respondents. The data analysis carried out was univariate analysis and bivariate analysis. The test used was the chi square statistical test with another alternative test, namely the Fisher Excat test with a significance level of p=0.02, HA was accepted because it was proven that there was a relationship between knowledge of pregnant women and attitudes with p<0.05. It was concluded that there is a relationship between nutritional status and the incidence of pneumonia in toddlers in the working area of the Woha Health Center. Based on the results of this study, it is best if health workers, especially midwives, work together with health agencies that carry out outreach activities in order to increase parents' knowledge and information regarding the treatment of pneumonia in toddlers.